KAUSA KEJAHATAN DAN UPAYA PENANGGULANGAN TINDAK PIDANA PENCURIAN TANAMAN PORANG (Studi Yuridis Kriminologis di Desa Sumber Bendo dan Klangon Kecamatan Saradan, Kabupaten Madiun) - Prija Djatmika Sri Lestariningsih Setiawan Nurdayasakti (Faculty of Law, Universitas Diponegoro, 2010)
Economics problems among society become complicated at the moment. Economic problems, especially poverty, can stimulate the people to commits crimes, such as theft. An example of this statement is a theft of